Ethical and legal considerations governing use of health data for quality improvement and performance management: a scoping review of the perspectives of health professionals and administrators - Tim Shaw; Kevin Leow; Ian Kerridge; Cameron Stewart; Anna Janssen; Kavisha Shah (BMJ Open Quality)
Background The rapid digitisation of healthcare has resulted in the capture of a vast amount of health data, which are increasingly being used for secondary purposes, such as quality improvement and performance management.Objectives This study examined the legal and ethical considerations that affect if and how health professionals and administrators implement and use their performance data from the perspective of these stakeholder groups.Eligibility criteria The search strategy focused on the use of health data (1) for quality improvement and performance management, (2) by health professionals and (3) discussion of ethicolegal concerns.Sources of evidence A scoping review was conducted of three medical databases (Medline, Scopus and Embase) in April 2023, updated in June 2024.Charting methods Included articles were first charted against 12 descriptive variables and then thematically analysed against the 16 substantive and procedural values of the Ethics Framework for Big Data in Health and Research (the Framework).Results We identified 16 articles that explored 5/7 procedural and 8/9 substantive values of the Framework. Health professionals were mostly concerned with the fairness of data comparisons defined as the use of accurate and risk-adjusted datasets and the contextualisation of performance data against clinical experiences. Health administrators additionally emphasised the importance of good governance and data stewardship to improving professional engagement with performance data, but privacy remains a key barrier.Conclusions The growing interest in using health data for quality improvement and performance management requires health services to address barriers to utilisation of performance data. Legal and ethical concerns must be balanced and prioritised in collaboration with end users for performance data to be accepted as a valid form of quality and performance assessment. Although privacy remains a key issue, these fears can be effectively managed by restricting public reporting on performance to only what is essential for public assurance.